Persepsi Belia Muslim Malaysia Terhadap Terorisme - Mohd Khairul Naim Che Nordin; Muhamad Syafriz Mhd Nazer; Ros Aiza Mohd Mokhtar; Che Zarrina Saari (Universiti Teknologi Malaysia (UTM), 2024)
Non-Indexed Publication